Evaluation of a protocol for eliciting narrative accounts of pediatric inpatient experiences of care. (29th January 2023) - Martino, Steven C.; Reynolds, Kerry A.; Grob, Rachel; Palimaru, Alina I.; Zelazny, Sarah; Slaughter, Mary E.; Rybowski, Lise; Parker, Andrew M.; Toomey, Sara L.; Schuster, Mark A.; Schlesinger, Mark
Abstract: Objective: To evaluate the measurement properties of a set of six items designed to elicit narrative accounts of pediatric inpatient experience. Data Sources: Data came from 163 participants recruited from a probability‐based online panel of U.S. adults. Participants were family members of a child who had an overnight hospital stay in the past 12 months. Study Design: Cross‐sectional survey with follow‐up phone interviews. Data Collection/Extraction Methods: Participants completed an online ( n = 129) or phone ( n = 34) survey about their child's hospitalization experience. The survey contained closed‐ended items from the Child Hospital Consumer Assessment of Healthcare Providers and Systems (Child HCAHPS) survey, followed by the six narrative items. Approximately 2 weeks after completing the survey, 47 participants additionally completed a one‐hour, semi‐structured phone interview, the results of which served as a "gold standard" for evaluating the fidelity of narrative responses. Qualitative content analysis was used to code narrative and interview responses for domains of patient experience and actionability. Principal Findings: The average narrative was 248 words ( SD = 319). Seventy‐nine percent of narratives mentioned a topic included in the Child HCAHPS survey; 89% mentioned a topic not covered by that survey; and 75% included at least one detailed description of an actionable event. Overall, there was 66% correspondence between narrative and interview responses. Correspondence was higher on the phone than in the online condition (75% vs. 59%). Conclusions: Narratives elicited from rigorously designed multi‐item sets can provide detailed, substantive information about pediatric inpatient experiences that hospitals could use to improve child and family experiences during pediatric hospitalization. They add context to closed‐ended survey item responses and provide information about experiences of care important to children and families that are not included in quantitative surveys.